Feasibility of delivering a randomized controlled trial of weighted blanket intervention to help agitation and disturbed sleep after brain injury - Edwards, Laura (Frontiers in Sleep, 2024)
Sleep disturbance and agitation are common after acquired brain injury (ABI). Weighted blankets may help these symptoms in other conditions, but have not been trialed in ABI. We aimed to determine acceptability and feasibility of weighted blankets to aid sleep and agitation after ABI. We recruited participants into a non-blinded, randomized controlled study in an NHS inpatient neurorehabilitation unit. Participants were randomized 1:1 to weighted blanket or standard hospital linen. Participants underwent observation of sleep (including actigraphy) and behavior over 11 nights. Of 10 participants randomized, seven participants completed the study. Only 1 participant tolerated the weighted blanket throughout and only three wore the actigraph for all nights of the study. Participants found the weighted blanket hot, heavy and uncomfortable. The study was terminated early due to poor tolerance. Delivery of a definitive trial in this format would not be feasible.